1982
DOI: 10.1111/j.1365-3083.1982.tb00643.x
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Numbers of HLA‐DR‐Positive T Lymphocytes in the Synovial Fluid and Synovial Tissue of Patients with Rheumatoid Arthritis and Juvenile Rheumatoid Arthritis

Abstract: Twenty to 40% of T cells from synovial fluid and synovial tissue and 3-11% of the peripheral blood T lymphocytes from patients with rheumatoid arthritis (RA) and juvenile rheumatoid arthritis (JRA) expressed HLA-DR antigens as detected by monoclonal anti-HLA-DR antibodies in direct immunofluorescence. Synovial fluid and synovial tissue T lymphocytes had a stimulating capacity comparable to that of non-T cells in the allogeneic primary mixed lymphocyte reaction (MLR). The MLR was inhibited by monoclonal anti-HL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 15 publications
3
29
0
Order By: Relevance
“…In this study, a fraction of SF T cells from patients with oligoarticular JA were found to express activation markers [2][3][4][5]. Therefore, such cells were preferentially expanded in the presence of low-dose rIL-2 and cloned.…”
Section: Discussionmentioning
confidence: 70%
“…In this study, a fraction of SF T cells from patients with oligoarticular JA were found to express activation markers [2][3][4][5]. Therefore, such cells were preferentially expanded in the presence of low-dose rIL-2 and cloned.…”
Section: Discussionmentioning
confidence: 70%
“…The SF leucocyte count in our patients ranged between 120 and 9200/ram 3 and 53.7% of the cells were PMNC. Forre et al [17] found increased CD3+ and HLA-DR+ T cells in SF of JCA patients. Venables [16] reported decreased counts of B cells and increased CD8+ cells in SF.…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that recognition of arthritogenic antigen presented in the context of a limited range of major histocompatibility complex molecules by T-cell receptors (TCRs) of disease-promoting T lymphocytes results in the triggering of a pathogenic immune response. The strong association between JRA and certain major histocompatibility complex class II specificities (3)(4)(5) and the histopathology of the diseased joint (6)(7)(8) (18) and the first-strand cDNA was synthesized as described (19).…”
mentioning
confidence: 99%